Hubungan Antara Indeks Massa Tubuh Dengan Kelincahan Pada Pemain Futsal Pria Usia 19-23 Tahun - Mahendra, Luhut; , Dwi Kurniawati, SSt.Ft, M.Kes; , Wahyuni, S.KM, S.Fis, M.Kes (2015)
Background: Agility is one of the important physical condition aspects in futsal sport. Agility has supporting factors like body height and body weight. With ideal body height and body weight, futsal player can achieve maximum performance. Body mass index can be used to measure the increasing of the body weight. Body mass index is the ratio between body weight and body height that measured from top of the head to the edge of foot. Goal: To find out the relationship between body mass index and agility of 19-24 years old futsal player. Benefit: the data can become references or suggestions for the development of medical world and sport especially on the relationship between body mass index and agility of futsal player. Method: This research using observational analytics with cross sectional approach. This research uses 50 samples, and takes the sample with purposive sampling, that take randomly with inclusion and exclusion. Statistic analysis that we use is fisher exact alternative chi square. Instrument for measure the agility is ilionis agility test. Result of the Research: The result of the research stated that there is relationship between body mass index with agility of futsal players within p < 0,05 is 0,039 so Ha accepted. This means that body mass index variable there is relationship with agility dependent variable. Conclusion: statistically show that body mass index was relationship with agility of 19-24 years old male futsal players UKM futsal Health Faculty Muhammadiyah University of Surakarta. Keywords: Body mass index, Agility, Male futsal players